PACU: Precision agriculture computational utilities - Caio L. dos Santos; Fernando E. Miguez (SoftwareX)
The field of precision agriculture relies on collecting and processing several types of data to assess temporal and spatial variability. We developed the pacu R package to provide a comprehensive and transparent framework for precision agriculture applications. The package includes functions to process and visualize yield monitor data from production and experimental fields. In addition, pacu facilitates the retrieval, processing, and visualization of satellite images from Copernicus Data Space. Lastly, there are functions to retrieve, summarize, and visualize long-term weather data. The current package is intended to facilitate the access by researchers and agronomists to routine precision agriculture computational utilities.